The importance of nurses' performance in the process of sterilization material in a hospital institution: An integrative review (Research, Society and Development, 2023)
Objective: To describe, based on scientific literature, everything that concerns the role of nurses in the sterilization material sector in a hospital institution, in order to better understand the entire process experienced by the nursing team. Methodology: This is an integrative literature review carried out from May to December 2023, using the following databases: VHL, LILACS, LILACS/MEDLINE, where articles in Portuguese were used between the years 2008 and 2023. The following descriptors were used: “Materials center”, “Sterilization”; "Nursing". Results and discussions: A total of 340 articles were found, after methodological rigor using the inclusion and exclusion criteria, 14 articles were selected, 11 articles in LILACS, 3 in LILACS/MEDLINE, after careful evaluation of the articles, the analysis was carried out in a descriptive way and predisposes the extraction of the following data: order number, author, title, periodical, study category, year of publication, where all articles highlight the importance of nursing action in the material sterilization process. Final considerations: It was concluded that the process of sterilizing hospital material requires a closer look from nurses, aiming for greater safety for patients, professionals and health services, mainly regarding tests and records of the sterilization process, practicing a reflective stance regarding the importance of your work.